Implementación del aplicativo web para la generalización de notificaciones instantáneas del desempeño académico en la Unidad Educativa San Francisco de Asís. - Díaz Ante, Jenny Soraya (2020)
Nowadays web appS are important because they present unlimited possibilities through the network in which they facilitate life with options such as emails, forums, chats, blogs among others that allow people to be more communicated and interrelated than time before. In such a way that SMS as a mass communication tools are increasingly popular. The objective of this technological proposal is the implementation of a web application for generalization of notifications on academic performance at San Francisco de Asís Educational Unit. For the development of this system Scrum methodology and the Uml unified language based on general concepts were used about the Php programming language, the Laravel open source framework for web applications developing and services, the MySQL database manager and the Nexmo platform for their respective message delivery allowed to establish a single standard at sending time to their legal representatives. The creation of this web application will help to keep informed about the academic performance of each student, so that a digital communication between the actors of the institution must be stablished.